Synthesis of perovskite-type high-entropy oxides as potential candidates for oxygen evolution - Schweidler, Simon; Tang, Yushu; Lin, Ling; Karkera, Guruprakash; Alsawaf, Alaa; Bernadet, Lucile; Breitung, Ben; Hahn, Horst; Fichtner, Maximilian; Tarancón, Albert; Botros, Miriam (Frontiers in Energy Research, 2022)
High-entropy materials offer a wide range of possibilities for synthesizing new functional ceramics for different applications. Many synthesis methods have been explored to achieve a single-phase structure incorporating several different elements, yet a comparison between the synthesis methods is crucial to identify the new dimension such complex ceramics bring to material properties. As known for ceramic materials, the synthesis procedure usually has a significant influence on powder morphology, elemental distribution, particle size and powder processability. Properties that need to be tailored according to specific applications. Therefore, in this study perovskite-type high-entropy materials (Gd0.2La0.2–xSrxNd0.2Sm0.2Y0.2) (Co0.2Cr0.2Fe0.2Mn0.2Ni0.2)O3 (x = 0 and x = 0.2) are synthesized for the first time using mechanochemical synthesis and a modified Pechini method. The comparison of different syntheses allows, not only tailoring of the constituent elements of high-entropy materials, but also to optimize the synthesis method as needed to overcome limitations of conventional ceramics. To exploit the novel materials for a variety of energy applications, their catalytic activity for oxygen evolution reaction was characterized. This paves the way for their integration into, e.g., regenerative fuel cells and metal air batteries.